INTENSE PULSED LIGHT (IPL) – TREATMENT STRATEGY FOR MEIBOMIAN GLAND DYSFUNCTION - Monika Dimitrova; Irina Kuneva (Journal of IMAB)
Meibomian gland dysfunction (MGD) is a primary cause of dry eye syndrome, as the meibomian glands produce lipids that maintain tear film integrity and reduce its evaporation. Blockage of these glands can result in symptoms associated with dry eye disease. Intense pulsed light (IPL) therapy is a novel treatment option for dry eye syndrome caused by MGD. Purpose. The purpose of our study is to assess the safety and effectiveness of IPL for treating dry eye syndrome caused by MGD in various age groups, by analyzing the non-invasive tear breakup time (NITBUT) and Schirmer's test results both before and after two IPL treatments. Materials and methods: A total of 120 subjects, each with varying degrees of MGD, underwent IPL treatment in both eyes. Each patient received two procedures spaced two weeks apart. Tear breakup time (TBUT) and Schirmer's test were evaluated at baseline and two weeks following the final treatment. Results: The majority of tests demonstrated improvement in key clinical parameters, including tear breakup time, Schirmer's test, meibum quality, and the Standard Evaluation of Eye Dryness Questionnaire. IPL therapy shows therapeutic potential for treating MGD, enhancing tear film quality, and alleviating dry eye symptoms. Conclusion: IPL presents a promising area for development, offering the potential for improved outcomes in patients with MGD, and is currently the focus of ongoing research.